Identification of canine norovirus in dogs in South Korea - Kwang-Soo Lyoo; Min-Chul Jung; Sun-Woo Yoon; Hye Kwon Kim; Dae Gwin Jeong (BMC Veterinary Research, 2018)
Abstract Background Canine noroviruses (CaNoVs) are classified into genogroups GIV, GVI, and GVII and have been detected in fecal samples from dogs since their first appearance in a dog with enteritis in Italy in 2007. CaNoVs may be a public health concern because pet animals are an integral part of the family and could be a potential reservoir of zoonotic agents. Nonetheless, there was no previous information concerning the epidemiology of CaNoV in South Korea. In the present study, we aimed to detect CaNoV antigens and to investigate serological response against CaNoV in dogs. Results In total, 459 fecal samples and 427 sera were collected from small animal clinics and animal shelters housing free-roaming dogs in geographically distinct areas in South Korea. For the detection of CaNoV, RT-PCR was performed using target specific primers, and nucleotide sequences of CaNoV isolates were phylogenetically analyzed. Seroprevalence was performed by ELISA based on P domain protein. CaNoVs were detected in dog fecal samples (14/459, 3.1%) and were phylogenetically classified into the same cluster as previously reported genogroup GIV CaNoVs. Seroprevalence was performed, and 68 (15.9%) of 427 total dog serum samples tested positive for CaNoV IgG antibodies. Conclusion This is the first study identifying CaNoV in the South Korean dog population.